Solution-Processed Pure Blue Thermally Activated Delayed Fluorescence Emitter Organic Light-Emitting Diodes With Narrowband Emission - Xu, Ting; Liang, Xiao; Xie, Guohua (Frontiers in Chemistry, 2021)
To satisfy the high color purity requirement of display technology with simply fabricated process, herein, solution-processed blue thermally activated delayed fluorescence (TADF) organic light-emitting diodes (OLEDs) with the narrow spectrum with a full width at half maximum (FWHM) of 32 nm and y color coordinate below 0.2 are demonstrated by employing a molecule containing boron and nitrogen) atoms (TBN-TPA) as the guest emitter in the emissive layer. The opposite resonance positions B-N atoms of TBN-TPA endows multi-resonance effect leading to high color purity.